Detection of radiation treatment of spices using Electron Spin Resonance Spectroscopy Technique: ESR detection of irradiated spices - Khan, A A; Shahid, M K (Journal of Spices and Aromatic Crops, 2021)
Use of ionising radiation for commercial sterilisation to increase the hygienic quality of spices is increasing worldwide. Among several detection methods, Electron Spin Resonance (ESR) spectroscopy is one of the reliable techniques for irradiated foods containing some hard and dried parts. Spices are therefore candidates of such a method and radiation treated spices can be detected. The purpose of the present work was to identify the radiation treatment of spices like cinnamon, cardamom, ginger and rosemary using the sensitive technique of ESR spectroscopy. The spice samples were irradiated to 5, 10, 15 and 20 kilogray (kGy) or unirradiated and the samples were dried in vacuum oven and were placed into quartztubes for ESR measurement. On measurements, the unirradiated samples were found to show the ESR-signal at g-value of 2.004 that is typical in case of plant foods containing cellulose. Whereas, the irradiated samples showed a formation of a new paramagnetic structure that appeared in the form of a triplet-signal, attributed to radiation-induced cellulose radical. The clear difference between the nature of ESR signals in case of unirradiated and irradiated samples provided the evidence of the radiation treatment of spices samples. It is therefore concluded that radiation treatment of spices can be identified using sensitive ESR spectroscopy during a storage period of three to ten months.